IMPLEMENTASI MANAJEMEN PENDIDIKAN KARAKTER DALAM MENGEMBANGKAN MINAT, SIKAP DAN PERILAKU POSITIF SISWA - Mustofa Aqil (UNISAN JURNAL, 2024)
Education Management in this case has a strategic role in determining the direction of development of a nation. So, the management of character education should be applied in every world of children’s lives, starting from family, school, even in their play environment. In this position, character education requires strong collaboration with the educational curriculum in schools, especially Madrasah Level Education where the education management that is implemented must be able to support the education of children’s positive attitudes and behaviors. Methods This research uses a qualitative approach with triangulation data collection techniques. The research location is the Nuruliman Margo Tani Education Foundation in SMA Sabillun Najah Musi Banyuasin Village . The results showed that the implementation of character education management in developing students’ interests, attitudes and behavior was based on objective planning with clear and specific goals, having regular education programs, developing activities in the form of intra-curricular, extracurricular, guidance and counseling of activity programs with the aim of as the formation of character education for students, improving students’ skills in the practice of humanizing humans and other skills. Determination of the management of character education in developing the interests, attitudes and positive behavior of students. in the form of long-term and short-term programs implemented by example, direction, assignment, habituation, and environment creation. This affects the character of the santri in the form of leadership, discipline, trust, sincerity and courtesy. These conditions support the creation of an environment that is healthy and conducive learning environment, everything that is heard, seen, and suggested by students are elements of education.